Integration of Public Speaking Skills in Business Communication: A Strategy to Improve Company Reputation - Astuti Itasari, Andri (Journal La Sociale, 2026)
This study aims to explore the role of public speaking skills in enhancing corporate reputation through strategic business communication. This study uses a Systematic Literature Review (SLR) approach involving the identification, evaluation, and systematic analysis of 50 articles, where six selected articles are the main focus based on the relevance and completeness of the text. The results of the study indicate that effective public speaking skills can strengthen emotional connections with the audience, increase public trust, and strengthen corporate reputation. In addition, communication strategies through strong public speaking narratives significantly contribute to crisis management and building relationships with stakeholders. This study also found that public speaking combined with social responsibility (CSR) communication creates positive perceptions of the company, strengthens customer loyalty, and increases the value of the organization's reputation. The contribution of this study to academic discussions is to strengthen the argument that public speaking skills are a strategic element in corporate reputation management. These findings provide a new perspective on the integration between public speaking and corporate communication strategies, which have often been separated in related research. This study also highlights the importance of public speaking in building transparency, trust, and emotional connections with various stakeholders, both internal and external. Thus, this study offers practical guidance for organizations in managing reputation through effective communication, as well as providing important insights for academics and practitioners to develop public speaking-based communication models in the digital era. This study provides a strong foundation for the development of innovative and relevant business communication strategies in an increasingly competitive global landscape..